Comparison of Perioperative Outcomes of Robotic-Assisted vs Laparoscopic Adrenalectomy for Pheochromocytoma: A Meta-Analysis - Xia, Zhongyou; Li, Jinze; Peng, Lei; Yang, Xiaoying; Xu, Yulai; Li, Xianhui; Li, Yunxiang; Zhang, Zongping; Wu, Ji (Frontiers in Oncology, 2021)
Objective To compare the efficacy and safety of robotic-assisted adrenalectomy (RA) and standard laparoscopic adrenalectomy (LA) for pheochromocytoma (PHEO). Methods We systematically searched the Cochrane Library, PubMed, Embase, and Science databases for studies published through January 2021. Controlled trials on RA and LA for PHEOs were included. The meta-analysis was conducted with the Review Manager 5.4 software. Results Four studies with 386 patients were included in the analysis. There were no significant differences in OT (WMD: 0.16; 95% CI: -28.50 to 28.82; I2 = 89%; P = 0.99), transfusion rate (OR: 0.70; 95% CI: 0.07 to 7.07; I2 = 64%; P = 0.77), conversion rate (OR: 0.44; 95% CI: 0.07 to 2.88; I2 = 0%; P = 0.39), complication rate (OR: 1.06; 95% CI: 0.62 to 1.82; I2 = 0%; P = 0.84) among patients undergoing RA and LA. However, compared with patients who underwent LA, patients who underwent RA had a shorter LOS (OR: -0.50; 95% CI: -0.55 to 0.45; I2 = 31%; P<0.01), less EBL (WMD: -0.85; 95% CI: -13.56 to -2.54; I2 = 44%; P<0.01), and fewer IHD (OR: 0.34; 95% CI: 0.17 to 0.70; I2 = 0%; P<0.01). Conclusion The RA for pheochromocytoma achieve better outcomes over LA in terms of safety and efficacy.